Facile preparation of Fe3C decorate three-dimensional N-doped porous carbon for efficient oxygen reduction reaction. (5th May 2020) - Ma, Guofu; Xie, Xuan; Sun, Kanjun; Peng, Hui; Cui, Shuzhen; Zhou, Xiaozhong; Wang, Qintao; Lei, Ziqiang
Abstract: Novel Fe3 C nanoparticles that decorate three-dimensional N-rich porous carbon (Fe3 C@3DNC) catalysts were designed and synthesized by double templates assisted high-energy ball milling and subsequent high-temperature pyrolysis for the oxygen reduction reaction (ORR). NaCl and Na2 SiO3 are used as the mixed template while Fe(NO3 )3 ·9H2 O and 2-Methylimidazole were used as the iron, nitrogen and carbon sources. The optimized Fe3 C@3DNC catalyst (Fe3 C@3DNC-1-900) had good ORR performance in alkaline medium, with an Eonest value of 0.968 V and E1/2 value of 0.861. In addition, the catalytic process exhibited selectivity–nearly four-electron transfer kinetics and possesses a lower Tafel slope compared to commercial Pt/C catalyst as well as good methanol tolerance. In addition, the Fe3 C@3DNC-1-900 catalyst also had excellent ORR activity (E1/2  = 0.72 V) and long-term stability (the half-wave potential only occurs at 10 mV after 5000 cycles) in acidic media. The good catalytic performance of the Fe3 C@3DNC-1-900 catalyst can be attributed to the 3D hierarchically porous structure and extremely high number of active sites around the porous carbon. The double template assisted high-energy ball milling strategy can be a promising and scalable method to prepare three-dimensional porous carbon-based composite materials for energy conversion and storage applications. Graphical abstract: Image 1 Highlights: Fe3 C decorate three-dimensional N-doped porous carbon are prepared by template assisted method. Highly active FeNx active site with Fe can be form in the Fe3 C@3DNC-1-900 catalyst. The abundant Fe3 C and N-doped species in Fe3 C@3DNC-1-900 are benefit for catalytic performance. The obtained Fe3 C@3DNC-1-900 catalyst exhibit an exceptionally outstanding ORR activity.